An evaluation of the properties of rotor forgings made from 26NiCrMoV115 steel - Balcar, Martin (Materiali in tehnologije, 2008)
The development and verification of production technology for the rotor forgings of compressors and generators demonstrate the significant effect of the forming of the input ingot on the final properties of the forgings. The measured yield strength and the strength limit show a trend of dependence on the sample's position in the rotor. Significant differences in the longitudinal as well as in the transversal directions over the cross-section of a forging have been found, especially for the transition temperature FATT Tsub50. The mechanical properties of experimental rotor forgings made of 26NiCrMoV115 steel indicate that the forming and heat-treatment processes can be optimized.
Keywords: plinske turbine; rotorji; gredi; kovanje; mehanske lastnosti